Vertical restraints: an examination of American and European rules - Campbell, Raphael Martin (2000)
Vertical restraints are arrangements concluded between undertakings operating at different levels of the manufacturing or distribution chain which restrict the conditions under which goods are purchased or sold. This work examines the antitrust treatment of these restraints in Europe and the United States of America.